2018
DOI: 10.1111/jfbc.12553
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bound phenolic from defatted Moringa oleifera seed flour on diet-induced hypercholesterolemic mice

Abstract: The effect of bound phenolic and catechins extracted from defatted Moringa oleifera seed (DMSF) flour on diet‐induced hypercholesterolemia was evaluated in this study. The animals (C57BL6 mice) were divided into four groups: group one received AIN 93M diet (control) group two received high‐fat cholesterol diet (HFCD), three and four received HFCD along with bound phenolic and catechins, respectively, through oral administration at the dose of 25 mg/kg body weight daily for 8 weeks. Blood and tissue analysis sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Moringa oleifera is widely utilized in alternative medicine for its antioxidant and health-promoting characteristics [ 60 ]. Its leaves are a good source of bioactive and phenolic substances, which have been shown to protect against chronic illnesses associated with oxidative damage [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera is widely utilized in alternative medicine for its antioxidant and health-promoting characteristics [ 60 ]. Its leaves are a good source of bioactive and phenolic substances, which have been shown to protect against chronic illnesses associated with oxidative damage [ 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moringa oleifera is commonly applied in folk medicine via its antioxidant and healt‐promoting properties. Yet, its biological activities are not limited to the antioxidant capacity (Pandu, Cherupanalli, & Muthukumar, ). M. oleifera leaves are a great source of bioactives and phenol compounds, such as flavonoids and phenolic acids.…”
Section: Discussionmentioning
confidence: 99%
“…We have further detailed the main phenolic compounds by HPLC after alkaline hydrolysis (Govardhan‐Singh, Negi, & Radha, 2013), with catechin as a main phenolic compound, in agreement with the composition given by the previous authors for kernel flour. Again, the results for whole seed flour were higher than those obtained for the kernel flour (7.15 vs. 3.40 mg/kg, respectively), indicating that shells are an important source of these compounds, whose positive effect in the lipid profile of diet‐induced hypercholesterolemic mice has been reported (Pandu, Cherupanalli, & Muthukumar, 2018). Our results are within the expected amounts based on Ijarotimi et al (2013) findings, but lower than the ones reported by Govardhan‐Singh et al.…”
Section: Resultsmentioning
confidence: 92%